2020
DOI: 10.1002/art.41140
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity Linked to Increase in Autoantibody Diversity in IgG4‐Related Disease

Abstract: Objective Four autoantigens have been described recently in IgG4‐related disease (IgG4‐RD): prohibitin, annexin A11, laminin 511‐E8, and galectin‐3. However, no external validation has been performed, and the possibility that some individuals break tolerance to more than 1 autoantigen has not been explored. We undertook this study to evaluate the relative frequencies of antibody responses against these autoantigens in order to explore the role of adaptive immune response in IgG4‐RD. Methods Autoantibody respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
(56 reference statements)
0
36
0
Order By: Relevance
“…Finally, several autoantigens have been described in IgG4-RD, including prohibitin, annexin A11, laminin 511, and galectin-3, but autoantibodies against these proteins are found at low frequency in patients’ serum and can also be measured in some healthy donors and mimicker conditions, bearing low specificity and sensitivity for diagnostic purposes 37383940100Table 1. gives an overview of traditional and novel biomarkers used for diagnosing IgG4-RD.…”
Section: Diagnosis Of Igg4 Related Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several autoantigens have been described in IgG4-RD, including prohibitin, annexin A11, laminin 511, and galectin-3, but autoantibodies against these proteins are found at low frequency in patients’ serum and can also be measured in some healthy donors and mimicker conditions, bearing low specificity and sensitivity for diagnostic purposes 37383940100Table 1. gives an overview of traditional and novel biomarkers used for diagnosing IgG4-RD.…”
Section: Diagnosis Of Igg4 Related Diseasementioning
confidence: 99%
“…In particular, patients with antibodies against two or more autoantigens (prohibitin, annexin A11, laminin 511-E8, and galectin-3) have marked IgG subclass elevations, complement consumption, and visceral organ involvement, indicating that severity of IgG4-RD is associated with an increased diversity of the autoantibody profile 100. Elevated serum concentrations of soluble interleukin 2 receptor, a surrogate marker of T cell activation, correlates with IgG4-RD activity and predicts response to glucocorticoids 169170.…”
Section: Management Of Igg4 Related Diseasementioning
confidence: 99%
“…All of the patients in our study population had AIP, whereas the population studied by Liu et al consisted of IgG4‐RD patients with involvement of various organs, including pancreatic involvement in only 32%. In this regard, we have found that the frequency of anti–laminin 511‐E8 autoantibody in patients with IgG4‐RD but without AIP was clearly low compared to the frequency in patients with AIP (Shiokawa M, et al: unpublished observations), whereas Liu and colleagues found no significant difference in laminin 511‐E8 autoantibody responses between patients with and those without pancreatic involvement . Finally, although the enzyme‐linked immunosorbent assay methods used for antibody measurement appear similar in both studies, some details might differ.…”
mentioning
confidence: 77%
“…We read with interest the article by Liu et al describing their study evaluating relative frequencies of antibody responses against 3 autoantigens in order to explore the role of adaptive immune response in IgG4‐related disease (IgG4‐RD) .…”
mentioning
confidence: 99%
See 1 more Smart Citation